A visual affective analysis of mass media interventions to increase antimicrobial stewardship amongst the public. Issue 1 (16th September 2018) - Langdridge, Darren; Davis, Mark; Gozdzielewska, Lucyna; McParland, Joanna; Williams, Lynn; Young, Mairi; Smith, Fraser; MacDonald, Jennifer; Price, Lesley; Flowers, Paul
Abstract : Objectives: In an innovative approach to improve the contribution of health psychology to public health we have analysed the presence and nature of affect within the visual materials deployed in antimicrobial stewardship interventions targeting the public identified through systematic review. Design: A qualitative analysis focused on the affective content of visual materials garnered from a systematic review of antibiotic stewardship ( k  = 20). Methods: A novel method was devised drawing on concepts from semiotics to analyse the affective elements within intervention materials. Results: Whilst all studies examined tacitly rely on affect, only one sought to explicitly deploy affect. Three thematic categories of affect are identified within the materials in which specific ideological machinery is deployed: (1) monsters, bugs, and superheroes; (2) responsibility, threat, and the misuse/abuse of antibiotics; (3) the figure of the child. Conclusions: The study demonstrates how affect is a present but tacit communication strategy of antimicrobial stewardship interventions but has not – to date – been adequately theorized or explicitly considered in the intervention design process. Certain affective features were explored in relation to the effectiveness of antimicrobial resistance interventions and warrant further investigation. We argue that further research is needed to systematically illuminate and capitalize upon the use of affect to effect behaviour change concerning antimicrobial stewardship. Statement of contribution What is already known on this subject? The (mis)use of antibiotics and consequent risk of antimicrobial resistance is a critical public health problem. If sufficient action is not taken, global society will face the 'post‐antibiotic' era, in which common infections will lead to death for many millions. Key desirable behavioural changes are decreased patient demands for antibiotics, use of them for targeted purposes alone, and compliance with prescribed dosing. There is a growth of interest in the role of affect in mass media interventions designed to engage publics and produce health‐related behavioural change. What does this study add? This article presents a novel analytic approach to understanding and intervening within behaviour change in public health that may complement other types of analysis. We present findings specifically from an 'affective' analysis based on semiotics in which we critically interrogated the visual imagery being deployed in mass media public health interventions concerning antimicrobial stewardship. Three thematic categories of affect are identified within the materials in which specific ideological machinery is deployed and that demonstrate some association with intervention effectiveness worthy of further investigation and testing.